Hubungan Pengetahuan Gizi Seimbang dan Asupan Zat Gizi Makro dengan Kejadian Gizi Kurang di SMPN 2 Kota Jambi - Rezkiani, Salsa; Jeki, Andicha Gustra; Hesty, Hesty (Prosiding Seminar Kesehatan Nasional, 2024)
Undernutrition is a condition of the body that lacks nutrients such as protein, carbohydrates, minerals, vitamins, and fats. WHO 2018 states that the number of malnutrition sufferers in adolescents in the world reaches 14.9%. Several factors that can cause malnutrition include nutrient intake and knowledge. The purpose of this study wasto determine the relationship between knowledge of balanced nutrition and macronutrient intake with the incidence of malnutrition in adolescents at SMPN 2 Jambi City. This type of research is quantitative using a cross sectional research design. The sample used was 80 respondents. The sampling technique is simple random sampling. This research was conducted in May 2024 at SMPN 2 Jambi City. The data analysis used was univariate and bivariate analysis using the correlation test. The results of this study showed that respondents who had knowledge of balanced nutrition with a deficient category were 56 (70%), less protein intake was 50 (62,5%), less fat intake was 54 (67.5%), less carbohydrate intake was 68 (85%) and the incidence of malnutrition was 29 (36.2%). The results of the Spearmen Correlation Test found that there was a relationship between balanced nutrition knowledge and the incidence of malnutrition (p = 0.017), there was arelationship between protein intake (p = 0.029), fat intake (p = 0.028) and carbohydrateintake (p = 0.029) with the incidence of malnutrition in adolescents at SMPN 2 Jambi City. In conclusion, there is a relationship between knowledge of balanced nutrition, protein intake, fat intake, and carbohydrate intake in adolescents at SMPN 2 Jambi City. It is recommended that adolescents be given education related to balanced nutrition and adolescents pay more attention to their food intake, because it can affect nutritional status.